2018
DOI: 10.1016/j.jjcc.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Transcarotid transcatheter aortic valve implantation: A systematic review

Abstract: The available data on TC TAVI show comparable technical feasibility with other traditional access routes, representing a viable alternative. However, the paucity of data warrants the need for larger randomized controlled trials to establish a firm conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 43 publications
3
36
2
Order By: Relevance
“…Patient preference and individual patient factors, such as age and small left ventricular outflow tract, and other factors not normally included in the currently used surgical scoring systems play a significant role. Additionally, compared with TAVR, SAVR continues to have absolute lower rates of residual paravalvular leakage, major vascular complications and new permanent pacemakers 22 (reported as ranging from 13.2 to 17.1%) 46, 47 . Lastly, this randomised evidence arises from the comparison of the most modern TAVR technology with old-fashioned conventional AVR through median sternotomy.…”
Section: Transcatheter Aortic Valve Replacements: Results and Comparimentioning
confidence: 99%
“…Patient preference and individual patient factors, such as age and small left ventricular outflow tract, and other factors not normally included in the currently used surgical scoring systems play a significant role. Additionally, compared with TAVR, SAVR continues to have absolute lower rates of residual paravalvular leakage, major vascular complications and new permanent pacemakers 22 (reported as ranging from 13.2 to 17.1%) 46, 47 . Lastly, this randomised evidence arises from the comparison of the most modern TAVR technology with old-fashioned conventional AVR through median sternotomy.…”
Section: Transcatheter Aortic Valve Replacements: Results and Comparimentioning
confidence: 99%
“…Transcarotid approach in terms of stroke risk is more controversial. Non-randomized trials found similar neurological outcomes (3.8% 30-day CVE) compared to an historically transfemoral cohort ( 42 ). However, recent evidence with a small number of patients ( n = 22) showed more than twice the number and total volume of new ischemic lesions evaluated by diffusion-weighted magnetic resonance imaging within the left hemisphere ( p < 0.01 for both) when performing TAVI through the left carotid artery ( 43 ).…”
Section: Predictors Of Cerebrovascular Events After Tavimentioning
confidence: 84%
“…However, recent meta-analyses and systematic reviews have suggested that the available data limit formal meta-analysis and, as such, they draw no firm conclusions regarding the safety and efficacy of this method. 31,32…”
Section: Trans-subclavian/transaxillarymentioning
confidence: 99%